Aminah The Greatest Love Pahit manis kisah hidup ibunda Muhammad Abdul Salam Al-Asyri;penerjemah Arifudin;penyunting Ghozi Mubarok - AL-ASYRI, Abdul Salam; Arifin; Mubarok, Ghozi (Pena Pundi Aksara, 2008)
x,282 hlm ilus 24 cm